Grouping trends of magnetic permeability components in their parallel evolution with microstructure in Ni0.3Zn0.7Fe2O4 - Idza Riati Ibrahim; Mansor Hashim; Rodziah Nazlan; Ismayadi Ismail; Wan Norailiana Wan Ab Rahman; Nor Hapishah Abdullah; Dr. Fadzidah Binti Mohd Idris; Mohd Shamsul Ezzad Shafie; Muhammad Misbah Muhamad Zulkimi (Elsevier, 2024)
Indexed by Scopus